Comparison of genomic abnormality in malignant mesothelioma by the site of origin. Issue 12 (12th September 2014) - Takeda, Maiko; Kasai, Takahiko; Enomoto, Yasunori; Takano, Masato; Morita, Kohei; Nakai, Tokiko; Iizuka, Norishige; Maruyama, Hiroshi; Ohbayashi, Chiho
Abstract : Aims: Malignant mesothelioma (MM) results from the accumulation of a number of acquired genetic events at the onset. In MM, the most frequent changes are losses in 9p21, 1p36, 22q12 and 14q32, and gains in 5p, 7p and 8q24 by comparative genomic hybridisation analysis. We have examined various genomic losses and gains in MM and benign mesothelial proliferation by fluorescence in situ hybridisation (FISH) analysis. 9p21 deletion was reported to be less frequent in peritoneal than in pleural MMs. This study analysed various genomic losses and gains in MM by the site of origin using FISH analysis. Materials and methods: We performed FISH analysis using paraffin-embedded tissues from 54 cases (40 pleural and 14 peritoneal) of MMs and compared the frequency of genomic abnormality by the site of origin. Results: 9p21 deletion was shown in 34 of 40 cases (85%) of pleural MMs, and was less frequent in five of 14 cases (36%) of peritoneal MMs (p<0.001) by FISH analysis. By contrast, 5p15 and 7p12 amplification was more significantly frequent in peritoneal than in pleural MMs. No difference between the two sites of MM in other genes was found. Conclusions: 9p21 homozygous deletion assessed by FISH has been reported to be useful for differentiating MM from reactive mesothelial proliferation, but it should be noted that 9p21 deletion was less frequent in peritoneal MM. Our study suggests that the pathway of the genetic abnormality might vary between pleural and peritoneal MM.